The nitrate/(per)chlorate relationship on Mars. Issue 6 (21st March 2017) - Stern, Jennifer C.; Sutter, Brad; Jackson, W. Andrew; Navarro‐González, Rafael; McKay, Christopher P.; Ming, Douglas W.; Archer, P. Douglas; Mahaffy, Paul R.
Abstract: Nitrate was recently detected in Gale Crater sediments on Mars at abundances up to ~600 mg/kg, confirming predictions of its presence at abundances consistent with models based on impact‐generated nitrate and other sources of fixed nitrogen. Terrestrial Mars analogs, Mars meteorites, and other solar system materials help establish a context for interpreting in situ nitrate measurements on Mars, particularly in relation to other cooccuring salts. We compare the relative abundance of nitrates to oxychlorine (chlorate and/or perchlorate, hereafter (per)chlorate) salts on Mars and Earth. The nitrate/(per)chlorate ratio on Mars is < 1, significantly lower than on Earth (nitrate/(per)chlorate > 10 3 ), suggesting not only the absence of biological activity but also different (per)chlorate formation mechanisms on Mars than on Earth. Key Points: Nitrate and perchlorate on Mars behave as they do in environments dominated by abiotic processes on Earth The nitrate/perchlorate ratio is vastly lower on Mars than on Earth due to high Martian perchlorate abundance, suggesting unique processes The nitrate/perchlorate ratio in Hesperian rocks could be compared to younger materials to detect ongoing production of either species